2019
DOI: 10.1038/s41598-019-48076-6
|View full text |Cite
|
Sign up to set email alerts
|

Glycan-immobilized dual-channel field effect transistor biosensor for the rapid identification of pandemic influenza viral particles

Abstract: Pandemic influenza, triggered by the mutation of a highly pathogenic avian influenza virus (IFV), has caused considerable damage to public health. In order to identify such pandemic IFVs, antibodies that specifically recognize viral surface proteins have been widely used. However, since the analysis of a newly discovered virus is time consuming, this delays the availability of suitable detection antibodies, making this approach unsuitable for the early identification of pandemic IFVs. Here we propose a label-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In addition, the assay responds specifically to SARS CoV-2 in presence of MERS CoV. Hideshima et al reported a glycan based FET biosensor which can detect both human H1N1 and avian H5N1 influenza viruses in nasal mucus [ 109 ]. Rapid detection in the wide concentration range 10 0.5 to 10 8.5 TCID 50 /mL was made possible by functionalizing the gate terminals with two different sialic acid containing glycans that recognize human and avian viruses respectively.…”
Section: Review Of Recent Electrochemical Biosensors For Eids and Re-mentioning
confidence: 99%
“…In addition, the assay responds specifically to SARS CoV-2 in presence of MERS CoV. Hideshima et al reported a glycan based FET biosensor which can detect both human H1N1 and avian H5N1 influenza viruses in nasal mucus [ 109 ]. Rapid detection in the wide concentration range 10 0.5 to 10 8.5 TCID 50 /mL was made possible by functionalizing the gate terminals with two different sialic acid containing glycans that recognize human and avian viruses respectively.…”
Section: Review Of Recent Electrochemical Biosensors For Eids and Re-mentioning
confidence: 99%
“…To selectively recognize target biomolecules or bioparticles, the gate insulator surface is functionalized with respective receptors (e.g., antibodies, antigens or ssDNA). the electrostatic detection of various intact virus particles, including several subtypes of influenza A [H1N1 (Hideshima et al, 2019;Park et al, 2019), H3N2 (Shen et al, 2012), H5N1 (Hideshima et al, 2019), H5N2 (Chiang et al, 2012)], human immunodeficiency virus (HIV) (Kim et al, 2019), rotavirus (Liu et al, 2013), Ebola (Jin et al, 2019), and SARS-CoV-2 (Seo et al, 2020). For instance, a SiNW biosensor for the rapid (within minutes) and low-cost diagnosis of seasonal flu that could detect H3N2 viruses in clinical, exhaled breath condensate samples down to ∼3 × 10 4 particles/mL, was developed by Shen et al (2012).…”
Section: Intact Virus Particle Detectionmentioning
confidence: 99%
“…LOD for virus detection was 0.025 HAU, which was two orders of magnitude lower than with conventional rapid human influenza virus test kits [ 130 ]. A similar two-channel device based on a semiconductor interface for immobilization of α-2,6-sialylactose and α-2,3-sialylactose was used for the detection of human (H1N1) and avian (H2N1) influenza viruses [ 131 ]. The portable device connected to a mobile phone via Bluetooth could measure the interaction in a label-free format with the integration seen in real time ( Figure 17 ).…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%
“…The portable device connected to a mobile phone via Bluetooth could measure the interaction in a label-free format with the integration seen in real time ( Figure 17 ). The device could detect influenza viruses at a concentration much lower than by using a device based on immunochromatography [ 131 ]. Another device for the detection of influenza relies on the compression of a polymer layer resulting in the induction of stress in the artificial layer causing a resonance frequency shift ( Figure 18 ) [ 132 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%